The Emotional State and Physical Condition of Indonesian College Students: An Emerging Situation during the Coronavirus Disease-19 Crisis in Indonesia - Arundhana, Andi Imam; Iqbal, Muhammad; Maharani, Siti Annisa; Syam, Aminuddin (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Since the first cases in Wuhan China have been reported, the Coronavirus disease (COVID)-19 cases increased exponentially over the world. This disease might affect physical and mental well-being. AIM: This study was aimed to examine the emotional state and physical condition of college students during the COVID-19 pandemic in Indonesia. METHODS: The study used a cross-sectional survey design in April 2020. The participants of the survey were adult that currently enrolled at one of the universities in Indonesia from diploma-1 to master’s degree. Information from a total of 1044 participants could be obtained. We used the developed self-reported questionnaire to collect information regarding socio-demographic, personal hygiene and healthy lifestyle, anthropometric measurement data, and depressive symptoms. Pearson Chi-square and Fisher’s exact test were performed using SPSS v.24 with a significant level of P < 0.05. RESULTS: This study found that 31.1% of participants are possible depressed. Of 1044 students, 35.3% were malnourished (16.5% underweight and 18.8% overweight/obese). Factors associated with depressive symptoms are sleep longer than usual, gathering with family members, and working (for income-generating). CONCLUSION: The COVID-19 probably affected the majority of Indonesian college students, especially for emotional and physical condition. The government should not neglect this group by providing clinical and social supports for their well-being.